Relationship between index properties and soil-water characteristic curves (SWCC) - Thng, Terence Xiong Jie (Nanyang Technological University, 2020)
Residual soils are commonly found in Singapore due to the tropical climate that has encouraged in-situ mechanical and chemical weathering of the rock formation. The high temperature and abundant rainfall experienced throughout the years have also resulted in the repeated drying and wetting cycles of residual soils. Residual soils are also unsaturated soils as they are commonly found above the ground water table within the unsaturated conditions. The engineering behaviour of unsaturated soils are known to be largely governed by the soil-water characteristic curves (SWCCs) and the SWCCs were observed by past researchers to be affected by the index properties of soil. Therefore, the objective of this study was to investigate the relationship between the index properties (grain-size distribution and Atterberg Limits) and SWCCs of residual soils. These relationships can thereafter be used by engineers to estimate the SWCCs based on the index properties rather than performing the SWCC tests in laboratory. In this study, index properties and SWCC tests were conducted on four soil samples (Mount Sinai, Tampines, Buangkok Link and Seletar Hill) from two main geological formations (Jurong Formation and Old Alluvium) in Singapore. Two advanced laboratory equipment, namely the small-scale centrifuge apparatus and three-dimensional scanner were also used to facilitate this study. The results indicate that the air-entry value increases with the increasing percentage of fines and Liquid Limit in residual soils. Moreover, the residual suction increases non-linearly with the increasing percentage of fines and Liquid Limit in residual soils.